Comparison of the mineral and fatty acid profiles of ostrich, turkey and broiler chicken livers. Issue 2 (3rd March 2016) - Majewska, D.; Szczerbińska, D.; Ligocki, M.; Bucław, M.; Sammel, A.; Tarasewicz, Z.; Romaniszyn, K.; Majewski, J.
Abstract: The aim of this study was to determine the mineral and lipid profiles in ostrich, turkey and broiler chicken livers. The highest concentrations of phosphorus, potassium and magnesium were found in turkey livers, at 3751.50, 2153.05 and 363.98 mg/kg fresh weight (FW), respectively, whereas ostrich livers were the richest in calcium (82.77 mg/kg FW). Ostrich liver was the richest source of iron, calcium, zinc and silicon, at 947.8, 82.77, 47.50, 36.69 mg/kg FW, respectively. Ostrich livers proved to be the richest source of long-chain fatty acids (5.18% C20:4n+6, 0.48% EPA and 1.08% DHA)